2021
DOI: 10.1016/j.amsu.2021.102573
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of utilising wound edge protector in open appendicectomy to prevent surgical site infection

Abstract: Background The rate of surgical site infection (SSI) differ with variable nature with appendicitis with a global incidence of up to 11%. Several randomised trials describe a significant reduction in incisional SSI using wound edge protectors (WEP), mainly in elective procedures. This study was designed to analyse WEP use in emergency open appendicectomy. Method This randomised controlled trial enrolled 200 patients who underwent emergency open appendicectomy. Permuted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…A total of 1365 relevant studies were screened, of which 28 studies between 1969 and 2021, met the inclusion criteria and were involved in the meta‐analysis 15‐42 . Data obtained from these studies were shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1365 relevant studies were screened, of which 28 studies between 1969 and 2021, met the inclusion criteria and were involved in the meta‐analysis 15‐42 . Data obtained from these studies were shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1365 relevant studies were screened, of which 28 studies between 1969 and 2021, met the inclusion criteria and were involved in the meta‐analysis. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Data obtained from these studies were shown in Table 2 . The selected studies included 6026 subjects with lower gastrointestinal surgery at the baseline of the studies; 3090 of them were using the wound protector, and 2936 were using no wound protector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). Six included trials were considered as high quality 15 , 17 , 19 , 23 , 38 , 40 , 13 were considered moderate quality 12 , 16 , 18 , 20–22 , 24–28 , 31 , 41 , and 2 were considered low quality 29 , 30 , 39 ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that dual-loop devices are more effective in reducing SSI incidence; however, there are limited available data on dual-ring devices, and so, sufficient robust high-quality testing is warranted 33 , 34 . This article includes newly published RCTs of high quality that employed dual-ring devices 38 , 40 , 41 . It has been suggested that double-ring devices might prevent SSI more effectively than single-ring devices 37 .…”
Section: Discussionmentioning
confidence: 99%